Peak temperatures of ultra-high temperature metamorphism of the Napier Complex, Enderby Land, East Antarctica, as deduced from porphyroclastic pyroxenes of meta-ultramafic rocks - Ishizuka, Hideo; Suzuki, Satoko; Nakamura, Aki (National Institute of Polar Research, 2002)
P(論文) In the Mt. Riiser-Larsen area of the Archaean Napier Complex, an ultra-high temperature (UHT) metamorphic complex, Enderby Land, East Antarctica, meta-ultramafic rocks occur as blocks and pods embedded in orthopyroxene felsic gneiss or garnet felsic gneiss and as thin layers intercalated with orthopyroxene felsic gneiss. They consist mainly of olivine, orthopyroxene, clmopyroxene and spinel with or without phlogopite. On the basis of the modal proportion of olivine and pyroxene, they are classified into peridotite and minor pyroxenite. These constituent minerals are generally medium- to coarse-grained with granular texture. Furthermore, some samples also contain coarse-grained but porphyroclastic chno- and orthopyroxenes that are sometimes armored locally by neoblastic pyroxenes. Chemical compositions of granular pyroxenes are similar to those of neoblastic varieties, which are, however, different from those of porphyroclastic pyroxenes; porphyroclastic clinopyroxenes are rich in Al_2O_3 but poor in CaO as compared with granular and neoblastic clinopyroxenes. The pyroxene thermometer yields 600-650℃ for granular and neoblastic pyroxenes, while porphyroclastic pyroxenes indicate about 1130℃. The former lower temperatures are interpreted as representing a closure temperature of the thermometer, while the latter higher temperatures indicate a peak metamorphic temperature of the Napier UHT metamorphism. departmental bulletin paper